The differences in learning outcomes in students' archery skills according to physiological ability - Widiyanto, Widiyanto; Setyawan, Hendra; Suharjana, Suharjana; Pavlovic, Ratko; Nowak, Agnieszka Magdalena; Susanto, Nugroho; Gusliana-HB, Gusliana-HB; Bin Shahri, Mohd Izwan; García-Jiménez, José Vicente (Jurnal Cakrawala Pendidikan, 2024)
This study aims to compare how students learn archery skills in terms of physiological ability factors arising from first, middle, and last shots. Arm muscular strength is one physiological ability aspect that affects archery skills. Physical fitness has a big impact on archery success or accomplishment. This comparative quantitative study aims to ascertain how much student learning outcomes for archery skills vary or differ from one another. Thirty individuals from five different classes of Physical Education, Health, and Recreation (2019/2020) were sampled using the cluster random sampling method. Inferential one-way ANOVA descriptive statistics were employed for data analysis in this study, with a significance threshold of Î± 0.05. The research results show a difference in the average of the three archery skills learning outcomes for the students. The differences are between the outcomes of the first shot (encroachment), middle shot, and final shot. The results of Tukey's post hoc follow-up test indicated that (1) there was a significant difference (p < 0.05) in the average shot result (encroachment) between the first and the middle shots; (2) there was a significant difference (p < 0.05) in the average shot result (increase) between the first and the last shots; and (3) there is no significant difference (p < 0.05) in the average shot results between the middle shot and the last shot (p < 0.05).